2010
DOI: 10.1063/1.3457475
|View full text |Cite
|
Sign up to set email alerts
|

Boron diffusion in magnetic tunnel junctions with MgO (001) barriers and CoFeB electrodes

Abstract: Boron diffusion out of the CoFeB layers in model systems with thick CoFeB and MgO layers grown by radiofrequency sputtering or electron-beam evaporation and in MgO-based magnetic tunnel junctions ͑MTJs͒ is probed after annealing by x-ray photoemission spectroscopy ͑XPS͒ and electron energy loss spectroscopy. Successive interfaces are exposed by ion milling the stacks, layer by layer, in the XPS system. Despite the presence of thick CoFeB and a high annealing temperature of 400°C, we found no boron in the MgO o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 18 publications
3
24
1
Order By: Relevance
“…[15][16][17][18] Meanwhile, the B atoms are pushed out of the CoFeB electrodes and then diffused into the MgO layers forming Mg-B-O spacer. [19][20][21][22][23] around (001) axis and compressing lattice slightly.…”
Section: -10mentioning
confidence: 99%
“…[15][16][17][18] Meanwhile, the B atoms are pushed out of the CoFeB electrodes and then diffused into the MgO layers forming Mg-B-O spacer. [19][20][21][22][23] around (001) axis and compressing lattice slightly.…”
Section: -10mentioning
confidence: 99%
“…CoFeB grows amorphous when sputtered, while MgO grows polycrystalline beyond five atomic layers with a pronounced (001) out-of-plane texture [12]. During annealing, boron from the CoFeB layer is assumed to diffuse away [13,14], and layers of FeCo(100) crystallize at the MgO(100) interface, with the MgO serving as a template for FeCo(100) grains. Theoretical studies have indicated that a single atomic layer of crystalline Fe at the interfaces of a crystalline MgO barrier should be sufficient to achieve a giant TMR ratio [15].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12]20 The adjacent MgO barriers cannot absorb boron, which maintains the amorphous nature of CoFeB. 25 Here we investigate the low frequency noise in 20 as free layer with high temperature postannealing, which was recently reported to improve the TMR ratio in DMTJs. 13 We also discuss the probability of applying DMTJs as magnetic field sensors, based on their noise characteristics.…”
mentioning
confidence: 99%
“…[10][11][12]20 The adjacent MgO barriers cannot absorb boron, which maintains the amorphous nature of CoFeB. 25 Here we investigate the low frequency noise in DMTJs, with TMR ratios as high as 222% for symmetric MgO layers and 250% for asymmetric MgO layers at room temperature. Both types of DMTJs have a similar noise level in the parallel state, and in the following we only focus on the DMTJs with symmetric MgO layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation